Guard cells in fern stomata are connected by plasmodesmata, but control cytosolic Ca2+ levels autonomously. Issue 1 (14th April 2018) - Voss, Lena J.; McAdam, Scott A. M.; Knoblauch, Michael; Rathje, Jan M.; Brodribb, Tim; Hedrich, Rainer; Roelfsema, M. Rob G.
Summary: Recent studies have revealed that some responses of fern stomata to environmental signals differ from those of their relatives in seed plants. However, it is unknown whether the biophysical properties of guard cells differ fundamentally between species of both clades. Intracellular micro‐electrodes and the fluorescent Ca 2+ reporter FURA2 were used to study voltage‐dependent cation channels and Ca 2+ signals in guard cells of the ferns Polypodium vulgare and Asplenium scolopendrium . Voltage clamp experiments with fern guard cells revealed similar properties of voltage‐dependent K + channels as found in seed plants. However, fluorescent dyes moved within the fern stomata, from one guard cell to the other, which does not occur in most seed plants. Despite the presence of plasmodesmata, which interconnect fern guard cells, Ca 2+ signals could be elicited in each of the cells individually. Based on the common properties of voltage‐dependent channels in ferns and seed plants, it is likely that these key transport proteins are conserved in vascular plants. However, the symplastic connections between fern guard cells in mature stomata indicate that the biophysical mechanisms that control stomatal movements differ between ferns and seed plants.